Plant migration under long‐lasting hyperaridity – phylogenomics unravels recent biogeographic history in one of the oldest deserts on Earth. Issue 5 (28th March 2022) - Böhnert, Tim; Luebert, Federico; Merklinger, Felix F.; Harpke, Dörte; Stoll, Alexandra; Schneider, Julio V.; Blattner, Frank R.; Quandt, Dietmar; Weigend, Maximilian
Summary: The post‐Miocene climatic histories of arid environments have been identified as key drivers of dispersal and diversification. Here, we investigate how climatic history correlates with the historical biogeography of the Atacama Desert genus Cristaria (Malvaceae). We analyze phylogenetic relationships and historical biogeography by using next‐generation sequencing (NGS), molecular clock dating, Dispersal Extinction Cladogenesis and Bayesian sampling approaches. We employ a novel way to identify biogeographically meaningful regions as well as a rarely utilized program permitting the use of dozens of ancestral areas. Partial incongruence between the established taxonomy and our phylogenetic data argue for a complex historical biogeography with repeated introgression and incomplete lineage sorting. Cristaria originated in the central southern part of the Atacama Desert, from there the genus colonized other areas from the late Miocene onwards. The more recently diverged lineages appear to have colonized different habitats in the Atacama Desert during pluvial phases of the Pliocene and early Pleistocene. We show that NGS combined with near‐comprehensive sampling can provide an unprecedented degree of phylogenetic resolution and help to correlate the historical biogeography of plant communities with cycles of arid and pluvial phases.